The role of stable isotopes in understanding rainfall interception processes: a review. (20th September 2016) - Allen, Scott T.; Keim, Richard F.; Barnard, Holly R.; McDonnell, Jeffrey J.; Renée Brooks, J.
Abstract : The isotopic composition of water transmitted by the canopy as throughfall or stemflow reflects a suite of processes modifying rainfall. Factors that affect isotopic composition of canopy water include fractionation, exchange between liquid and vapor, and selective transmittance of temporally varying rainfall along varying canopy flowpaths. Despite frequent attribution of canopy effects on isotopic composition of throughfall to evaporative fractionation, data suggest exchange and selection are more likely the dominant factors. Temporal variability in canopy effects is generally consistent with either exchange or selection, but spatial variability is generally more consistent with selection. However, most investigations to date have not collected data sufficient to unambiguously identify controlling processes. Using isotopic data for improved understanding of physical processes and water routing in the canopy requires recognizing how these factors and processes lead to patterns of isotopic variability, and then applying this understanding toward focused data collection and analysis. WIREs Water 2017, 4:e1187. doi: 10.1002/wat2.1187 This article is categorized under: Science of Water > Methods Abstract : Canopy interception results in evaporation and heterogeneous water inputs to the soil; the variability in water isotopes in throughfall and stemflow can improve understanding of within‐canopy processes.